Numerical Study of the Effects of Heat Loss and Solid Thermal Conductivity on Syngas Production for Fuel Cells - Xiaolong Wang; Mengmeng Yu; Zunmin Li; Zhen Wang; Xiuxia Zhang; Junrui Shi; Xiangjin Kong; Jinsheng Lv (Batteries)
Syngas can be used as feedstock for efficient energy conversion in solid oxide fuel cells (SOFCs). In the current paper, the conversion efficiency of methane to synthesis gas (H2 and CO) within a two-layer porous media reactor is investigated by a one-dimensional two-temperature model. A detailed chemical reaction mechanism GRI-Mech 1.2 is used to describe the chemical processes. Attention is focused on CO2 content in the methane/air mixture, heat loss to the surroundings, and solid thermal conductivity on temperature distribution and conversion efficiency. Numerical results show that addition of CO2 to the methane/air mixture improves the conversion efficiency. For a molar ratio of CO2/CH4 = 1, the conversion efficiency reaches 44.8%. An increase in heat loss to the surroundings leads to a decrease in conversion efficiency. A greater solid thermal conductivity can improve the conversion efficiency.